The deceivers - Haddix, Margaret Peterson (Haddix, Margaret Peterson. Greystone secrets, 2020)
Told from separate viewpoints, as Finn, Emma, and Chess Greystone and Natalie Mayhew, ages eight to thirteen, continue their quest to rescue their mothers they must return to the alternate dimension where truth is illegal.